MEASURES TO OPTIMIZE ROAD TRAFFIC AND CALCULATIONS OF ENVIRONMENTAL SAFETY AT SOME PROBLEM SECTIONS OF ROAD-ON-DON ROAD INFRASTRUCTURE - Durov, R. S.; Varnakova, E. V.; Kobzev, K. O.; Kobzeva, N. D. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2019)
The article discusses the problem areas of the Combine Builders Square in Rostov-on-Don and possible measures that could improve traffic at this roundabout. Environmental indicators were calculated after carrying out the proposed measures to reduce CO emissions by cars. A comparative analysis of indicators before and after the events. The data obtained made it possible to establish how much the proposed measures to optimize traffic will help to reduce CO emissions by cars.